2020
DOI: 10.1055/a-1161-0372
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Maca (Lepidium meyenii/Lepidium peruvianum) Using a Mass Spectral Fingerprinting, Metabolomic Analysis, and Genetic Sequencing Approach

Abstract: AbstractMaca (Lepidium meyenii, synonym L. peruvianum) was analyzed using a systematic approach employing principal component analysis of flow injection mass spectrometry fingerprints (no chromatographic separation) to guide the selection of samples for metabolite profiling and DNA next generation sequencing. Samples consisted of 39 commercial maca supplements from 11 manufacturers, 31 unprocessed maca tubers grown in Peru and China, and a historic non-tuber maca sample from Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Unfortunately, this misinterpretation was restated by Tafuri et al (2019). Concerning the product with m/z 215.15, and Geng et al (2020) proposed the structure of 1-benzyl-2-ethyl-4,5-dimethylimidazolium, which was also erroneously named as 1-dibenzyl-2-ethyl-4,5-dimethylimidazolium. Apart from these mistakes in chemical names, it can be deduced that these studies did not consider the possibility of substitution on both N-1 and N-3, and therefore, a substituent was erroneously located in position C-2 instead of N-3.…”
Section: Molecular Networking and Metabolomics Analysismentioning
confidence: 99%
“…Unfortunately, this misinterpretation was restated by Tafuri et al (2019). Concerning the product with m/z 215.15, and Geng et al (2020) proposed the structure of 1-benzyl-2-ethyl-4,5-dimethylimidazolium, which was also erroneously named as 1-dibenzyl-2-ethyl-4,5-dimethylimidazolium. Apart from these mistakes in chemical names, it can be deduced that these studies did not consider the possibility of substitution on both N-1 and N-3, and therefore, a substituent was erroneously located in position C-2 instead of N-3.…”
Section: Molecular Networking and Metabolomics Analysismentioning
confidence: 99%
“…Finally, 24 miscellaneous compounds were identified in Maca extract including amino acids, organic esters, sugars, and benzyl isocyanate (Table ). Their identities were confirmed by comparing their retention times and fragmentation patterns with data given in the literature, , besides searching the available online databases.…”
Section: Results and Discussionmentioning
confidence: 85%
“…However, significant research has been conducted on the glucosinolate fraction, most likely because of its occurrence throughout different phenotypes of maca, such as yellow, red, purple, and black varieties [19,72]. Although there is a noticeable color distinction by sight, multiple studies have suggested that the varying glucosinolates in maca hypocotyls, such as those seen with the distinct phenotypes and at specific altitudes, may be identifiers for the individual maca phenotypes [39,68,72,103]. The predominant colors of maca and select phytochemicals.…”
Section: Glucosinolatesmentioning
confidence: 99%